The Impacts of Library Services on Interlibrary Loan Requests Canceled due to Local Availability. Issue 5 (20th October 2019) - Kim, Hae Min; Wiggins, John; Sadusky, Lynda
Abstract: Interlibrary loan (ILL) services receive requests for resources that are available locally and form a major portion of canceled requests. The purpose of this study is to examine the relationship between requests canceled due to local availability and three aspects to identify impacts on ILL. The authors explored library service aspects such as collection format, the link resolver knowledge base, and discovery system functionality for potential influence on requests for locally available resources. Quantitative methods were used to identify evidence of different aspects' impact through analysis of ILL borrowing request data. The most important finding was that the discovery system had impact on ILL services by improving retrievability of locally available resources published recently. The results suggest that a modern discovery system can efficiently provide more relevant results sourced from a carefully curated set of authoritative resources, save users' time to access available materials, and reduce library staff members' time and effort. This study will be helpful to libraries through its analysis of library services that impact the cancelation of ILL requests due to local availability and how those services may influence service improvement.